Implementation of Regional Regulations on Handling Homelessness and Beggars in Palu City - Nasrullah, Nasrullah; Rachmad, Rachmad; Syukur, Muhammad (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
The purpose of this study was to determine the Implementation of Regional Regulation Number 3 of 2018 concerning Handling of Vagrant and Beggars in Palu City. The research approach uses descriptive qualitative. Data were collected through observation, interviews, and documentation. The theory used in this research is the theory by Donald Van Metter and Carl Van Horn. The results found that the implementation of Palu City Regional Regulation No. 3/2018 has not been maximized, this is due to four factors. First, the handling of vagrants and beggars is still incidental. Second, the lack of budget in handling vagrants and beggars. Third, the lack of information or socialization to the community regarding criminal acts that violate local regulations. Fourth, the lack of public understanding of the objectives of the policy where the community does not report to the Social Service regarding the presence of vagrants and beggars who are still roaming the streets.